2012
DOI: 10.1038/onc.2012.517
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical Notch signaling activates IL-6/JAK/STAT signaling in breast tumor cells and is controlled by p53 and IKKα/IKKβ

Abstract: Notch signaling is frequently hyperactivated in breast cancer, but how the enhanced signaling contributes to the tumor process is less well understood. In this report, we identify the proinflammatory cytokine interleukin-6 (IL-6) as a novel Notch target in breast tumor cells. Enhanced Notch signaling upregulated IL-6 expression, leading to activation of autocrine and paracrine Janus kinase/signal transducers and activators of transcription signaling. IL-6 upregulation was mediated by non-canonical Notch signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 54 publications
4
106
0
Order By: Relevance
“…However, concentration of Il6 in the supernatant of control cells was minimal and the neutralizing Il6 antibody had no impact on chondrocyte gene markers expression in the absence of Notch, suggesting that basal levels of Il6 are dispensable for chondrocyte function. Induction of Il6 by Notch is in agreement with previous studies carried out in bone marrow stromal cells, macrophages and breast cancer cells, and confirms that Il6 is a direct target gene of Notch signaling 26,48,49 .…”
Section: Discussionsupporting
confidence: 91%
“…However, concentration of Il6 in the supernatant of control cells was minimal and the neutralizing Il6 antibody had no impact on chondrocyte gene markers expression in the absence of Notch, suggesting that basal levels of Il6 are dispensable for chondrocyte function. Induction of Il6 by Notch is in agreement with previous studies carried out in bone marrow stromal cells, macrophages and breast cancer cells, and confirms that Il6 is a direct target gene of Notch signaling 26,48,49 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast in glioma-initiating cells, a PDGF-driven signaling axis involving NO-dependent inhibitor of differentiation 4 (ID4) has been shown to promote JAGGED1–NOTCH activity [59]. Related, both direct and non-canonical regulation of IL-6 expression by Notch has been previously reported [60, 61]. As it is well established that generation of HSCs requires multiple Notch signaling inputs [62], it will be interesting to investigate whether Notch signaling may be a part of the Hif1α-PDGFRβ signaling axis in regard to the ability of IL-6 to enhance production of HSPCs.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 regulates cancer stem cell (CSC) self‐renewal and promotes breast CSC survival and proliferation when activated by the Notch, Wnt, Hedgehog and TGF‐β signaling pathways . A clinical study showed that IL‐6 is a novel Notch target gene in breast tumor cells and that hyper‐activated Notch signaling upregulates IL‐6 via the JAK/STAT3 pathway when p53 is mutated . High nuclear Notch1 ICD (intracellular domain of the Notch receptor) immunoreactivity, enhanced IL‐6 mRNA and pSTAT3 levels were observed in a panel of BC tissue samples from ER‐α and PR negative patients .…”
Section: Activation Of Stat3 Through Secretion Of Cytokinesmentioning
confidence: 99%